Measles outbreak in a vaccinated or never vaccinated children aged 1-5 years in Khyber Pakhtunkhwa (KPK), Pakistan (Lower dir, Upper Dir and Bajawar): Chains of transmission of virus and role of vaccine failure - Subedi, Dharma D. (International Journal of Pharmaceutical & Biological Archive, 2022)
This study aimed to estimate the level of failures of measles vaccine or the children were never vaccinated against the measles in KPK (Lower Dir, Upper Dip, and Bajawar) aged 1–5 years. The outbreak of the measles among the children in lower Dir is very high. We carried out in all three districts which covered 467 children mostly aged 1–5 years in KPK during the month of March–July, 2014. Compared to the past year with 2014 (n = 467), the prevalence of the measles cases were very high (n = 1400) in 2013. Spread of measles virus is highest in the month of March–May 80% (375 of 467). The highest numbers of the measles cases 74% (347 of 467) were reported. In temperate areas, cases typically occur at the end of winter and the beginning of spring. The prevalence of measles in male and female children was nearly equal. Finally, we have observed that those children who were suffering from measles were mostly unvaccinated aged <3 years having acute malnutrition, Vitamin A deficiency, and parasitic infestation.